Реінжиніринг бізнес-процесів як засіб економічного розвитку підприємств - Дідух, Сергій; Дуковська, Яна (Odesa National University of Technology, 2025)
The article explores the essence of the concept of "business process reengineering" and considers its role in the management of a modern enterprise. The key principles of reengineering, its stages, methods and tools of implementation have been presented. The advantages and disadvantages of reengineering, as well as the challenges that companies may face when implementing it, have been considered in detail. The need and prospects for implementing reengineering at Ukrainian enterprises in the context of modern economic challenges, in particular in war conditions, have been substantiated. Real cases of reengineering application in international and Ukrainian companies from various fields of activity have been described, which allows to assess the effectiveness of this tool. The results of the implementation of reengineering as an effective mechanism for adapting enterprises to changes in the external environment, increasing their competitiveness, and optimizing business processes have been analyzed. The purpose of this article is to study business process reengineering as a key tool for improving the efficiency of enterprises.